On the brink of the reform of the Spanish academic evaluation system: Recalling the past to avoid mistakes in the present - Delgado-López-Cózar, Emilio (Anuario ThinkEPI, 2022)
This essay provides some reflections on the origin of the current scientific evaluation system in Spain, focusing on an analysis of the system of selection and accreditation of university faculty. This system was put in place to prevent academic inbreeding. The thesis that this is mainly a centralized system is rebutted: although accreditation is indeed centralized, faculty selection is carried out by universities themselves. It is argued that we cannot fully trust universities to establish policies that are immune to localism and nepotism if they are not held fully responsible for their actions. The functional imbalance that exists in Spanish university teaching staff is highlighted. Among the activities currently carried out by university professors (teaching, research, knowledge transfer, and management), research is the most highly valued in evaluation programs. More specifically, publications are key to launch and advance careers in the academic environment. The success of the program of sexenios (six-year assessment periods), which serves not only as an incentive for productivity but also as an instrument to establish scientific reputation and academic hierarchy, has contributed to this situation. Other features of the current evaluation system in Spain are the predominance of individual-level evaluation and the use of bibliometric indicators as the final quality values. The Spanish academic evaluation system chose to give preference to individual-level evaluation. Once again, the origin of this approach can be found in the introduction of teacher and researcher productivity salary supplements in 1989. Spanish academics grew up in a culture of individual-level evaluation where they had to obtain their jobs through competitive examinations and were rewarded with bonuses on the basis of personal achievements. Quantitative criteria appeared as the necessary antidotes to curb nepotism. In a country lacking infrastructure and a culture of evaluation, quantitative indicators ensured objectivity and efficiency in the processes of selection and evaluation of publications, and, indirectly, a minimum amount of rigor and relevance of the research itself. The thoughts exposed here are accompanied by suggestions that might help guide the necessary reform of the scientific evaluation system.